Multiple Routes of Bluetongue Virus Egress - Thomas Labadie; Edward Sullivan; Polly Roy (Microorganisms, 2020)
Bluetongue virus (BTV) is an arthropod-borne virus infecting livestock. Its frequent emergence in Europe and North America had caused significant agricultural and economic loss. BTV is also of scientific interest as a model to understand the mechanisms underlying non-enveloped virus release from mammalian and insect cells. The BTV particle, which is formed of a complex double-layered capsid, was first considered as a lytic virus that needs to lyse the infected cells for cell to cell transmission. In the last decade, however, a more in-depth focus on the role of the non-structural proteins has led to several examples where BTV particles are also released through different budding mechanisms at the plasma membrane. It is now clear that the non-structural protein NS3 is the main driver of BTV release, via different interactions with both viral and cellular proteins of the cell sorting and exocytosis pathway. In this review, we discuss the most recent advances in the molecular biology of BTV egress and compare the mechanisms that lead to lytic or non-lytic BTV release.